Envisioning History: Helen Maria Williams’ Peru and Charlotte Smith’s Beachy Head - Rosenova, Rayna (Romanticism on the Net, 2021)
The debate about the value of history and romance occupied a central place in eighteenth- and nineteenth-century discourses. Both historical and fiction writing aimed to provide narrative frameworks that would help explain the rapidly changing contexts of modernity and people’s understanding of these changes. Although history was generally considered a male province, women writers incorporated historical material in their works to address social and political issues. This article discusses the uses of history in Helen Maria Williams’ and Charlotte Smith’s poetry, namely Williams’ epic Peru (1784), later revised as Peruvian Tales (1823), and Smith’s Beachy Head (1807). It focuses on how Williams and Smith used poetry as a vehicle to explore the connection between the past, the present, and the future by manipulating historical fact and evoking significant events as contemporaneous with the current political situation to address issues such as militarism, nationhood, and empire. It examines how Williams and Smith blurred the boundaries between the historical past and the present, while also merging the grand narrative of history with the little narratives of individual histories to negotiate the relationship between the two and interrogate the moral implications of progress.